Expression of Matrix Metalloproteinases and Their Tissue Inhibitors in Peripheral Blood Leukocytes and Plasma of Children with Nonalcoholic Fatty Liver Disease - Joanna B. Trojanek; Jacek Michałkiewicz; Renata Grzywa-Czuba; Wojciech Jańczyk; Lidia Gackowska; Izabela Kubiszewska; Anna Helmin-Basa; Aldona Wierzbicka-Rucińska; Mieczysław Szalecki; Piotr Socha (Mediators of Inflammation)
Gene expression profiles of matrix metalloproteinases (MMPs) and their tissue inhibitors (TIMPs) were evaluated in peripheral blood leukocytes of children with nonalcoholic fatty liver disease (NAFLD). Gene expression patterns were correlated with their plasma protein counterparts, systemic parameters of liver injury, and selected markers of inflammation. The MMP-2, MMP-9, MMP-12, MMP-14, TIMP-1, TIMP-2, TGF-β, and IL-6 transcripts levels were tested by the real-time PCR. Plasma concentrations of MMP-9, TIMP-1, MMP-9/TIMP-1 ratio, MMP-2/TIMP-2 ratio, sCD14, leptin, resistin, IL-1 beta, and IL-6 and serum markers of liver injury were estimated by ELISA. The MMP-9, TIMP-2 expression levels, plasma amounts of MMP-9, TIMP-1, and the MMP-9/TIMP-1 ratio were increased in children with NAFLD. Concentrations of AST, ALT, GGT, and leptin were elevated in serum patients with NAFLD, while concentration of other inflammatory or liver injury markers was unchanged. The MMP-2 and MMP-9 levels correlated with serum liver injury parameters (ALT and GGT concentrations, respectively); there were no other correlations between MMP/TIMP gene expression profiles, their plasma counterparts, and serum inflammatory markers. Association of MMP-2 and MMP-9 expression with serum liver injury parameters (ALT, GGT) may suggest leukocyte engagement in the early stages of NAFLD development which possibly precedes subsequent systemic inflammatory responses.